La recherche en temps réel : projet ECHO pour francophones - Détermination des besoins des fournisseurs de services desservant les communautés franco-ontariennes afin de créer un programme de formation en français sur le traitement des dépendances - CAMH-Evidence Exchange Network (2023)
fs-ref-orig: CAMH-Evidence Exchange Network. (2023). La recherche en temps réel : projet ECHO pour francophones - Détermination des besoins des fournisseurs de services desservant les communautés franco-ontariennes afin de créer un programme de formation en français sur le traitement des dépendances. https://kmb.camh.ca/fr/eenet/documentation/la-recherche-en-temps-reel-projet-echo-pour-francophones fs-code-orig: CAMH-Evidence Exchange Network-2023a

Research as it Happens : ECHO project for Francophones - Assessing the needs of service providers working with Franco-Ontarian communities to create a French-language, substance use management training program - CAMH-Evidence Exchange Network (2023)

L'offre active de services de santé mentale en français en Ontario et au Manitoba : les rôles clés des instruments et des outils - Cardinal, Linda; de Moissac, Danielle; Deschênes-Thériault, Guillaume (Administration publique du Canada / Canadian Public Administration, 2023)
Cet article présente les données d'un sondage réalisé en 2019 sur la connaissance des gestionnaires et des professionnels œuvrant dans le domaine de la santé mentale en Ontario et au Manitoba de leurs obligations linguistiques et des outils qui favorisent la pratique de l'offre active de services français. L'étude permet de souligner que plus les professionnels et les gestionnaires comprennent leurs obligations, tant en Ontario qu'au Manitoba, plus ils peuvent profiter des outils existants pour s'en acquitter. L'étude montre qu'il existe en effet un lien entre la connaissance des obligations et l'utilisation des outils pour faire de l'offre active de services de santé mentale en français. Elle permet aussi d'insister sur le rôle clé des outils pour faire de l'offre active de services en français.

Collective Identity Profiles: The Case of Francophones in Manitoba - Levesque, Annabel; Gueye, N’deye Rokhaya; Rivard, Étienne; de Moissac, Danielle; Archambault, Hélène (Minorités linguistiques et société / Linguistic Minorities and Society, 2023)
Abstract This quantitative study seeks to explore collective identity profiles that emerge among French-speaking adolescents and young adults in Manitoba. A total of 493 participants completed a questionnaire measuring their level of identification with Francophone and Anglophone identities, their perception of continuity with respect to the future of the French language and culture in Manitoba, and their mental wellbeing. The results of a cluster analysis revealed four collective identity profiles, namely Bilingual Optimist, Franco-Dominant Optimist, Indifferent Pessimist, and Anglo-Dominant Pessimist. Participants who belonged to each of these profiles differed in terms of their age, their mother tongue, the type of school they attended, and their gender. Moreover, collective identity profiles were linked to participants’ mental wellbeing, with those in the Bilingual Optimist profile and those in the Franco-Dominant Optimist profile demonstrating a significantly higher level of mental wellbeing compared to the other two profiles. Keywords: collective identity profiles, mental wellbeing, Francophone minorities, adolescence, young adulthood Résumé Cette étude quantitative visait à explorer les profils identitaires collectifs qui émergent naturellement chez les adolescents et les jeunes adultes francophones du Manitoba. Un total de 493 participants ont rempli un questionnaire mesurant leur niveau d'identification aux identités francophone et Anglophone, leur perception de continuité quant à l'avenir de la langue et de la culture françaises au Manitoba, et leur bien-être mental. Les résultats d'une analyse de classification ont révélé quatre profils identitaires collectifs émergeant, soit Bilingue optimiste, Franco-dominant optimiste, Indifférent pessimiste et Anglo-dominant pessimiste. Les participants appartenant à chacun de ces profils se distinguent par leur âge, leur langue maternelle, le type d'école qu'ils fréquentent et leur genre. De plus, les profils identitaires collectifs étaient liés au bien-être mental des participants, avec ceux du profil Bilingue optimiste et ceux du profil Franco-dominant optimiste ayant un niveau de bien-être mental significativement plus élevé par rapport aux deux autres profils. Mots-clés : profils identitaires collectifs, bien-être mental, minorités francophones, adolescents et jeunes adultes

Living in a liminal space: Experiences of 2SLGBTQ + official language minority Canadians during the COVID-19 pandemic - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya; Hardy, Stephan; Avanthay-Strus, Jacqueline (Culture, Health & Sexuality, 2023)
The intersecting identities of those identifying with multiple minorities, such as 2SLGBTQ + and ethnolinguistic minorities, bring individuals to have unique experiences, especially concerning health and wellness. This topic is particularly poorly understood among French-speaking official language minority 2SLGBTQ + populations in Canada. Hence, this study was conducted to generate insights into their needs and experiences, through the lens of intersectionality. This quantitative community-based study, a first of its kind in Western Canada, describes the sociodemographic profile, experiences of discrimination and stigmatisation, and needs and challenges pertaining to mental health and social supports of this double minority group. Data were obtained by an online survey conducted in the Canadian province of Manitoba in June 2020. The participant sample was largely homogenous: most were under the age of 55 years, white, educated, and from urban areas. Many reported experiencing dual marginalisation, feeling unaccepted by both of their minority communities (Francophone and 2SLGBTQ+). A sense of isolation, as well as a lack of social connectedness and psychological support, were often reported. Social initiatives and mental health support within environments proactively affirming of the official language of the minority and inclusive of diverse 2SLGBTQ + identities are needed.